Lifelong Learning and Metacognition in the Assessment of Pre-service Teachers in Practice-Based Teacher Education - Matsumoto-Royo, Kiomi; Ramírez-Montoya, Maria Soledad; Glasserman-Morales, Leonardo David (Frontiers in Education, 2022)
Initial teacher education should prepare pre-service teachers to develop effective teaching and lifelong learning tendencies. This study aimed to identify the component qualities and skills to consider in pre-service teachers' assessment processes that promote lifelong learning and develop metacognition skills. For this, it analyzed how the planned and implemented actions by the teacher educators in Practice-Based Teacher Education Programs promoted metacognition and lifelong learning in the pre-service teachers. The method was a mixed explanatory sequential design. Quantitative and qualitative instruments were applied. Information was obtained from the learning and assessment resources (72 syllabi and 14 assessment tasks) and pre-service teachers’ opinions (survey: n = 231, interviews: n = 8). The findings identified three main components: (i) authentic and relevant assessment tasks, (ii) prior communication of instructions and evaluation criteria, and (iii) frequent performance-focused feedback from peers and teacher educators during and at the end of assignments. The study results can be valuable in teacher education programs to strengthen assessment processes, promote lifelong learning tendencies, and develop metacognitive skills among the teachers in training.